India-U.S. strategic cooperation in the Indo-Pacific region - Chaki, Iranda; Garlick, Jeremy; Burešová, Hana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
This Thesis summarises the relationship between the United States of America and India, focusing on their strategic relations in the Indo-Pacific region. It tracks down the history of their relationship, with the help of historical analysis and the theory of realism. This thesis analyses whether the new bonding relations between the two states are genuine or the United States using India against China to fulfill their goals in the Indo-Pacific region.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses